2019
DOI: 10.1007/s10661-019-7274-x
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and macroelement contents in the liver of farm and wild animals and the health risks involved in liver consumption

Abstract: The paper presents the macroelement (Al, Ca, Cu, Fe, K, Mg, Mn, Na, P, and Zn) and microelement (As, Cd, Co, Cr, Hg, Mo, Ni, Pb, and Sn) contents found in the liver of wild animals (boar and deer) and farm animals (rabbit, chicken, duck, cow, goat, and turkey). Statistically, the differences in element contents between the two groups were not significant (at p = 0.05), with the exception of Fe, K, Mg, Cd, Hg, Mo, and Pb. The liver of farm animals contained more Al, Cu, K, Mg, Na, Cr, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
15
0
1
Order By: Relevance
“…Similar values were also reported by Pilarczyk et al [29]. Kicińska et al [15] reported that in scenarios with daily and weekly consumption of animal liver, the final HI calculated for children was approx. 3.5 times higher than for adults.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar values were also reported by Pilarczyk et al [29]. Kicińska et al [15] reported that in scenarios with daily and weekly consumption of animal liver, the final HI calculated for children was approx. 3.5 times higher than for adults.…”
Section: Discussionsupporting
confidence: 86%
“…3.5 times higher than for adults. Kicińska et al [15] reported a potential risk to health associated with the consumption of liver from game animals (HI > 1). In contrast, Lazarus et al [48] indicated that consumption of game meat and liver in Croatia did not pose a health risk to consumers, regardless of the exposure scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our study was conducted to obtain additional information on this topic. However, the literature about micro- and macronutrients in the liver of farm animals [ 45 ] shows the dependence of substance concentrations on the environment and feed factors.…”
Section: Discussionmentioning
confidence: 99%
“…As, Cd, Co, Cr, Hg, Ni, and Pb were selected in this study based on previous studies of trace element composition of Lebanese bread [1,13] and based on the Lebanese bread standard Libnor, NL 240 [23]. In contrast to heavy metals known to be toxic, such as Pb, Cd or Hg, some elements, such as Cr and Co, are essential elements giving benefit to the body, the liver being a valuable source of elements [24]. Co is a transition metal with two oxidation states Co (II) and Co (III) and is essential as part of vitamin B12 (cobalamin) involved in folate and fatty acid and the metabolism of proteins and nucleic acids [25].…”
Section: Introductionmentioning
confidence: 99%